Reconnaissance studies of micro hydro potential in Malaysia - Hussein I.; Raman N. (IEEE Computer Society, 2023)
Malaysia is blessed with abundant streams and rivers flowing from highland areas, thus promise it with a lot of hydro power potential. To date Malaysia had utilized these potential in the range of large and mini hydropower but very few in the micro hydro range. This paper presents the results of reconnaissance studies carried out to identify the micro hydro potential sites in Malaysia. The reconnaissance studies were conducted with data from the Department of Survey and Mapping Malaysia, (JUPEM) and Metrological Department Malaysia. All the identified streams were located in areas which are accessible and/or showed evidence of settlements. Only streams with high head i.e. above 50m, were considered in this study. From the reconnaissance studies, a total of 149 sites were identified. However, the energy demand for micro hydro was found not significant as most areas in Malaysia are electrified. Still, micro hydro generation may serve as alternative renewable energy source in future amid rising electricity cost.